HNS, a nuclear-cytoplasmic shuttling sequence in HuR - Fan, Xinhao Cynthia (The National Academy of Sciences, 1998)
Proteins are transported into and out of the cell nucleus via specific signals. The two best-studied nuclear transport processes are mediated either by classical nuclear localization signals or nuclear export signals. There also are shuttling sequences that direct the bidirectional transport of RNA-binding proteins. Two examples are the M9 sequence in heterogeneous nuclear ribonucleoprotein A1 and the heterogeneous nuclear ribonucleoprotein K shuttling domain (KNS) sequence in heterogeneous nuclear ribonucleoprotein K, both of which appear to contribute importantly to the export of mRNA to the cytoplasm. HuR is an RNA-binding protein that can stabilize labile mRNAs containing AU-rich elements in their 3′ untranslated regions and has been shown to shuttle between the nucleus and cytoplasm (18, 19). We have identified in HuR a shuttling sequence that also possess transcription-dependent nuclear localization signal activity. We propose that HuR first may bind AU-rich element-containing mRNAs in the nucleus and then escort them through the nuclear pore, providing protection during and after export to the cytoplasmic compartment.